1978
DOI: 10.1111/j.1600-0765.1978.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resultant tissue type following the intraoral transplantatin of various lyophilized soft tissues

Abstract: Epithelial regeneration was studied in Rhesus monkeys following the placement of fresh autogenous and lyophilized allogeneic soft tissue grafts in alveolar mucosa recipient sites. Two months postoperatively, histologic evaluation of biopsied graft areas showed that the autogenous free gingival graft controls, lyophilized allogeneic skin, and lyophilized allogeneic gingiva generally demonstrated a keratinized surfrace and other attributes of gingival‐type tissue. Lyophilized allogeneic mucosa universally yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…In agreement with prior studies of devitalized grafts, 18,19,35 the function of ADM is considered a biologic bandage or a scaffold at best. Contrary to the notion of some previous studies, 24,36 the authors believe that viability of the connective tissue is essential for a graft to fully express the capability of coding for keratinized epithelium.…”
Section: Comparison Of Changes In Adm and Fgg Groupscontrasting
confidence: 58%
“…In agreement with prior studies of devitalized grafts, 18,19,35 the function of ADM is considered a biologic bandage or a scaffold at best. Contrary to the notion of some previous studies, 24,36 the authors believe that viability of the connective tissue is essential for a graft to fully express the capability of coding for keratinized epithelium.…”
Section: Comparison Of Changes In Adm and Fgg Groupscontrasting
confidence: 58%
“…Allograft materials, especially skin preparations, were used for gingival augmentation procedures. [30][31][32][33][34][35][36][37][38][39] A major advantage of ADMA over skin preparations is the absence of the undesirable dead cells with their associated Class I and II HLD antigens and potential transmission of cell-associated viruses. Also, ADMA has essentially undamaged collagen and elastin matrices, making it completely biocompatible.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 It has been claimed that ADMA possesses several significant advantages over other allograft materials, especially over the previously used freeze-dried skin. [30][31][32][33][34][35][36][37][38] Based on several case reports in oral and periodontal surgery and clinical experience in plastic surgery, it has also been observed that ADMA consistently integrates into the host tissue; it maintains structural integrity of the tissue and revascularizes via preserved vascular channels.…”
mentioning
confidence: 99%
“…Because an adequate amount of keratinized tissue has not been defined yet, the decision to augment the width of keratinized gingiva around dental implants and teeth still depends on the clinician's choice and the planned surgical and prosthetic treatment. Historically, the methods to augment keratinized tissue included: (i) an apically positioned flap (APF); (ii) an APF in combination with autogenous tissue, and (iii) an APF in combination with allogenic tissue (Friedman 1962; Edel 1974; Yukna & Sullivan 1978).…”
mentioning
confidence: 99%